Signature files indexing technique on Malay text / Ahmad Azuan Muhammad Kamil - Muhammad Kamil, Ahmad Azuan (2009)
Information retrieval is the study of determining and retrieving document from a collection in order to satisfy the user's need, usually expressed in natural language. A search engine is an invaluable tool in the context of information retrieval, because it enables the handling of large numbers of data, and provides people with a tool to access various kinds of information at the tip of their fingers. In information retrieval, a text operation called indexing is applied to the documents needed to be retrieved, in order to aid with the retrieval process by making it easier to search through the documents available. Signature files is an indexing technique which transforms a document into a form represented by superimposed bit strings called signatures. A hadith is a record of the traditions or sayings of Prophet Muhammad S.A.W, generally revered by Muslims, and considered as a second source of religious guidance after the al-Quran. There are many hadith search engine available on the web, but most of it are in English or Arab, and only few are in Malay. This study proposes the use of signature files to develop a search engine prototype for Malay hadith text documents. The efficiency of the prototype is evaluated by testing it using a number of queries. The uses of this prototype will aid people in the society by providing them with understanding of various knowledge, which hopefully will lead them to a better life.